O teatro performativo: a construção de um operador conceitual - Leandro Geraldo da Silva Acacio (2011)
The object of this dissertation is the conceptual analyzer, performative theater, formulated by Franc-Canadian researcher Josette Féral. The performative theater is approached along this research as a tool of reflection and analysis of some scenic contemporary practices. In these circumstances, our goal is to systematize Férals research, which is still in process of elaboration. To Féral, the concept of performativity is the center of the debate about art and the contemporary theater. Féral uses two visions of performance to construct her notion of performativity. The first vision is cultural and anthropologic and follows a course by Performance Studies, divulged by the American director and intellectual Richard Schechner. The second vision is focused around artistic/aesthetic concepts, and it sources from the field of performance art. The dissertation also shows a reflection of one of the hallmarks of the current performative theater which is working with features of the tangibleestablishing the idea of event (occurrence). By bringing the tangible (real) to the scene, the performance can create a sudden break of illusion (theatricality), thus creating a disorder in the paradigms of the traditional representation in theater.